Conformation-dependent charge transport through short peptides. Issue 5 (28th January 2021) - Stefani, Davide; Guo, Cunlan; Ornago, Luca; Cabosart, Damien; El Abbassi, Maria; Sheves, Mordechai; Cahen, David; van der Zant, Herre S. J.
Abstract : Machine-learning analyses enable identifying signatures of peptide conformers in single molecule electron transport experiments. Abstract : We report on charge transport across single short peptides using the Mechanically Controlled Break Junction (MCBJ) method. We record thousands of electron transport events across single-molecule junctions and with an unsupervised machine learning algorithm, we identify several classes of traces with multifarious conductance values that may correspond to different peptide conformations. Data analysis shows that very short peptides, which are more rigid, show conductance plateaus at low conductance values of about 10 −3 G 0 and below, with G 0 being the conductance quantum, whereas slightly longer, more flexible peptides also show plateaus at higher values. Fully stretched peptide chains exhibit conductance values that are of the same order as that of alkane chains of similar length. The measurements show that in the case of short peptides, different compositions and molecular lengths offer a wide range of junction conformations. Such information is crucial to understand mechanism(s) of charge transport in and across peptide-based biomolecules.